2023
DOI: 10.1186/s12985-023-02125-9
|View full text |Cite
|
Sign up to set email alerts
|

Cervical carcinogenesis risk association of HPV33 E6 and E7 genetic variations in Taizhou, Southeast China

Abstract: Background Human papillomavirus (HPV) 33 belongs to the Alphapapillomavirus 9 (α-9 HPV) species group, which also contains types 16, 31, 35, 52, 58 and 67. The purpose of this study was to investigate the genetic variations of HPV33 and to explore its carcinogenicity among women in Taizhou, Southeast China. Methods Exfoliated cervical cells were collected for HPV genotyping. Only single HPV33 infection cases were selected, and their E6 and E7 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Since HPV33 has the highest prevalence in females aged 40–44 who developed ICC. Recent study showed that cervical carcinogenesis risk was associated with HPV33 E6 and E7 genetic variations ( Yan et al, 2023 ). Special attention should be paid to HPV33 screening and vaccination strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Since HPV33 has the highest prevalence in females aged 40–44 who developed ICC. Recent study showed that cervical carcinogenesis risk was associated with HPV33 E6 and E7 genetic variations ( Yan et al, 2023 ). Special attention should be paid to HPV33 screening and vaccination strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Since HPV33 has the highest prevalence in females aged 40-44 who developed ICC. Recent study showed that cervical carcinogenesis risk was associated with HPV33 E6 and E7 genetic variations (Yan et al, 2023). Special attention should be paid to HPV33 screening and vaccination strategy.…”
Section: Discussionmentioning
confidence: 99%